IMPLEMENTATION OF BALANCED NUTRITION EDUCATION FOR PREGNANT WOMEN IN AN EFFORTS TO PREVENT STUNTING IN BLANG ASAN VILLAGE, PEUSANGAN COMMUNITY HEALTH CENTER WORKING AREA, BIREUEN REGENCY - Nurhidayati; Herrywati Tambunan; Zulfa Hanum; Khairatul Umaira; Salsabila Nisa; Najma Nazira (Jurnal Pengabdian Bangsa, 2026)
This community service activity was carried out in Blang Asan Village, the working area of ​​the Peusangan Health Center , Bireuen Regency , with the aim of improving the knowledge , attitudes , and skills of pregnant women , breastfeeding mothers , and mothers of toddlers in implementing balanced nutrition as an effort to prevent stunting. This activity was motivated by the continued discovery of nutritional problems in the community , such as low knowledge about balanced nutrition , consumption patterns that are not yet diverse , and the continued presence of mothers at risk of Chronic Energy Deficiency (CED). The method of implementing the activity included lectures , interactive discussions , demonstrations , and direct practice . This activity was attended by 45 participants consisting of pregnant women , breastfeeding mothers , and mothers of toddlers . Evaluation was carried out through pretests and post-tests to measure the increase in knowledge , as well as measuring the Upper Arm Circumference (MUAC) to determine the nutritional status of participants . The results of the activity showed a significant increase in knowledge , where the good knowledge category increased from 22.2% to 66.7%. In addition , as many as 75.6% of participants showed a positive attitude . towards the implementation of balanced nutrition . The results of nutritional status measurements showed that 93.3% of participants were in the normal category , while 6.7% were at risk of KEK. The level of participant participation was also relatively high , with 80.0% of participants actively participating in all series of activities . This activity had a positive impact in increasing public understanding and awareness of the importance of balanced nutrition . Thus , community- based nutrition education carried out in a participatory and applicable manner can be an effective strategy in supporting stunting prevention efforts , especially in rural areas .